Colorectal cancer incidence and mortality after negative fecal immunochemical tests by age 70: A prospective observational study. Issue 6 (1st June 2021) - Zorzi, Manuel; Battagello, Jessica; Fiore, Anna Rita; Memo, Laura; Senore, Carlo; Rugge, Massimo
Abstract: Limited endoscopy capacity usually represents the main barrier to the extension of screening to subjects older than 70, given the high positivity rate in this age group. We assessed CRC incidence and mortality by number of previous negative fecal immunochemical tests (FIT) among subjects turning 70. We selected persons aged 70 years who had received their last screening invitation when they were 68 or 69 years old within the population‐based screening program in the Veneto region of Italy. Subjects with a positive FIT were excluded. We calculated 10‐year cumulative CRC incidence and mortality in cohorts of subjects having performed zero, one, two or three negative FITs over the last three screening rounds before turning 70. Out of 117 858 subjects included in the study (46.4% men), 33.7% had never participated in screening (zero negative FITs), 23.3% had had one‐negative FIT, 20.1% two‐negative FITs and 22.9% three negative FITs. The 10‐year cumulative CRC incidence was 29.7 per 1000 subjects with zero FITs, and respectively, 14.5, 11.7 and 9.6 per 1000 subjects with one, two and three negative FITs. The corresponding figures for 10‐year cumulative mortality were 9.3, 3.5, 2.2 and 2.1 per 1000 in the four study cohorts. Figures were roughly double for men than for women for all the study cohorts. In order to use more efficiently limited endoscopy resources, and to minimize the potential harms related to false positive results in the elderly, screening among people aged 70 to 74 might be restricted to those with zero previous negative FITs. Abstract : What's new? Limited endoscopy capacity represents a barrier to the extension of screening coverage to people aged 70 to 74, despite the high positivity rate in this age group. In this study, the 10‐year cumulative colorectal cancer incidence and mortality were significantly higher in a cohort of 69‐year‐old individuals who never participated in screening compared to subjects with one, two, and three previous negative fecal immunochemical tests (FITs). Restricting screening among 70 to 74‐year‐olds to those without previous negative FITs could make the utilisation of limited endoscopy resources more efficient and minimise the potential harms related to false‐positive results in the elderly.